6,5 - \(\frac{9}{4}\) : x +
=> 6,5 - 9/4 : x = 2 - 1/3 = 5/3
=> 9/4 : x = 6,5 - 5/3 = 0.5
=> x = 9/4 : 0.5 = ?
đến đó bạn tự tính nhé
Học Tốt !
\(a,\text{ }6,5-\frac{9}{4}\text{ : }x+\frac{1}{3}=2\)
\(\frac{13}{2}-\frac{9}{4}\text{ : }x+\frac{1}{3}=2\)
\(\left(\frac{13}{2}+\frac{1}{3}\right)-\frac{9}{4}\text{ : }x=2\)
\(\frac{41}{6}-\frac{9}{4}\text{ : }x=2\)
\(\frac{9}{4}\text{ : }x=\frac{41}{6}-2\)
\(\frac{9}{4}\text{ : }x=\frac{29}{6}\)
\(x=\frac{9}{4}\text{ : }\frac{29}{6}\)
\(x=\frac{27}{58}\)
\(6,5-\frac{9}{4}\text{ : }x+\frac{1}{3}=2\)
\(\frac{13}{2}-\frac{9}{4}\text{ : }x+\frac{1}{3}=2\)
\(\frac{13}{2}+\frac{1}{3}-\frac{9}{4}\text{ : }x=2\)
\(\frac{41}{6}-\frac{9}{4}\text{ : }x=2\)
\(\frac{9}{4}\text{ : }x=\frac{41}{6}-2\)
\(\frac{9}{4}\text{ : }x=\frac{29}{6}\)
\(x=\frac{9}{4}\text{ : }\frac{29}{6}\)
\(x=\frac{27}{58}\)